Application Of Micro Perforated Panel On The Safety Earmuff - Yew, Jia Jing (Universiti Sains Malaysia, 2021)
Safety earmuff is a common personal hearing protectors used in the working industries to protect workers from hearing losses. One of the disadvantages of the safety earmuff is it is not suitable to be used in hot, humid, or dusty environment. The foam lining of the safety earmuff, which is made of porous material, tends to disintegrate overtime. Micro-Perforated Panel (MPP) is proposed as the substitution for the foam lining material due to its acoustic characteristic, durable and lightweight characteristic. Experimental result shows that the MPP has better SAC and STL performance compared to the foam with averaged 26.44 dB STL improvement. MPP also shows improvement in SAC and the acoustic characteristic has an absorption bandwidth, which can be controlled by the parameters thickness (t), perforation diameter (d), cavity depth (D) and perforation ratio (σ). This shows that the acoustic characteristic of MPP can be modified to have better SAC at the desired frequency, especially for low to mid frequency application. Sound transmission loss analysis is performed on the earcup level of the earmuff, with MPP applied onto the earcup. Result shows that the foam lining only provides minimal attenuation improvement to the earcup while MPP earcup significantly changes the acoustic characteristic of the earcup, with an average improvement of 12.63 dB attenuation. The STL curve of the MPP earcup shows a major improvement in the mid and high frequency range (500 Hz – 4000 Hz) and a slight improvement in the low frequency range (below 500 Hz). The experimental results obtained conclude that the MPP-PHP is a potential substitution for the conventional earmuff and the acoustic characteristic of the MPP-PHP can be varied based on the application. More research should be done to evaluate the acoustic performance of the MPP-based personal hearing protectors.